2008
DOI: 10.1002/j.2168-9830.2008.tb00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Teaching Approaches on Learning Approaches of Construction Engineering Students: A Comparative Study between Hong Kong and Mainland China

Abstract: Teaching and learning contexts influence the learning process and determine the learning outcome or product. Teaching approaches may vary across different engineering and science courses and students. This study was aimed at understanding the differences in teaching approaches between two regions (Hong Kong and mainland China) and their relevant impacts on the learning process in construction engineering education. An exploratory survey was conducted on construction engineering students in China to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…Andrade (2006) suggests that the change to student-centered teaching can be a slow process. Indeed, contrary to earlier studies (Watkins, 2000;Biggs, 1994), the later studies do show that Chinese students are adapting to the student-centered teaching (Xiao, 2006;Leung & Lu, 2008;Zhang, 2006), which promotes critical thinking.…”
Section: R Hocontrasting
confidence: 47%
See 2 more Smart Citations
“…Andrade (2006) suggests that the change to student-centered teaching can be a slow process. Indeed, contrary to earlier studies (Watkins, 2000;Biggs, 1994), the later studies do show that Chinese students are adapting to the student-centered teaching (Xiao, 2006;Leung & Lu, 2008;Zhang, 2006), which promotes critical thinking.…”
Section: R Hocontrasting
confidence: 47%
“…Chinese students prefer the teacher-centered teaching methodology, which is consistent with findings from Nield (2004) and Leung and Lu (2008). It must be taken into consideration that teaching is not a one-way street and students must be able to learn from the instructors if the teaching is to be effective.…”
Section: R Homentioning
confidence: 58%
See 1 more Smart Citation
“…Results of a comparative study also lend some support to these observations. Specifically, Leung et al (2008) compared the teaching approaches in Hong Kong and mainland China. They found that instructors in mainland China tended to see teaching as an act of 'transferring' (i.e.…”
Section: Chinese Tertiary Teachers' Goals and Teaching Approachesmentioning
confidence: 99%
“…Less work has been done in Asia and specifically China. Some work has been done in Taiwan [5] and comparing Hong Kong and mainland Chinese construction engineering students [6]. Although popular misconceptions persist that Asian students are rote learners and resistant to innovative active pedagogies, research has shown this to be untrue for students in Hong Kong [7,8].…”
Section: Introductionmentioning
confidence: 99%